Climate Observing During Canada's Empires, 1742–1871: People, Places and Motivations. Issue 1 (30th November 2020) - Slonosky, Victoria; Mayer-Jouanjean, Isabelle
Abstract : page_1 other A wealth of pre-Confederation weather and climate observations were recorded in Canada by individuals and institutions during both the French and British empires. This scientific heritage came about for a number of reasons. For instance, the Hudson's Bay Company wanted to reduce operating costs by having their posts in Canada's north-west become self-sufficient in agriculture. Others wished to save lives from cholera or shipwrecks, or to satisfy curiosity about the ever-present debate concerning anthropogenic climate change. Today, historical climate observations can be found in many diverse locations. Despite our rich scientific heritage, turning archival paper and ink observations into scientific data remains an enormous technical challenge. This challenge falls to our generation, both to use this heritage to investigate the historical context of current climate change and variability, and to use the digital resources in development today to safeguard our scientific heritage for future generations.